Asphaltene Precipitation Investigation Using a Screening Techniques for Crude Oil Sample from the Nahr-Umr Formation/Halfaya Oil Field - A. Ahmed, Moammed; H. Abdul-Majeed, Ghassan; K. Alhuraishawy, Ali (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Many oil and gas processes, including oil recovery, oil transportation, and petroleum processing, are negatively impacted by the precipitation and deposition of asphaltene. Screening methods for determining the stability of asphaltenes in crude oil have been developed due to the high cost of remediating asphaltene deposition in crude oil production and processing. The colloidal instability index, the Asphaltene-resin ratio, the De Boer plot, and the modified colloidal instability index were used to predict the stability of asphaltene in crude oil in this study. The screening approaches were investigated in detail, as done for the experimental results obtained from them. The factors regulating the asphaltene precipitation are different from one well to another, from the high-pressure-temperature reservoir to surface conditions. All these factors must be investigated on a case-by-case basis. Because the Halfaya oil field is still developing its petroleum sector, modelling, and forecasting the phase behavior and asphaltene precipitation is crucial. This work used crude oil bottom hole samples with an API of equal to 27 from a well in the Halfaya oil field/Nahr-Umr formation to create a thermodynamic model using Multiflash software. The data included the compositional analysis, the PVT data, and reservoir conditions. The thermodynamic model of asphaltene phase behavior was proposed using the Cubic-Plus association equation of state. All the screening techniques’ results revealed the presence of an asphaltene precipitation issue (asphaltene unstable), which was confirmed by a thermodynamic fluid model. The aim of this paper is to predict the problem of asphaltene precipitation so that future proactive remedial methods can be developed to decrease the time and expense associated with it.